Zirconia sintered body and manufacturing method thereof

A zirconia sintered body with a controlled monoclinic crystal ratio and lattice structure addresses the trade-off between hardness and workability by ensuring the surface is easily processable and the interior is durable, enhancing both machinability and resistance to wear and scratches.

JP2025010099APending Publication Date: 2025-01-20TOSOH CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024107443
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-06
Filing Date
2024-07-03
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

There is a trade-off relationship between the hardness and workability of zirconia sintered bodies, where high hardness is required for scratch resistance and wear resistance, while low hardness is needed for improved machinability during processing.

Method used

A zirconia sintered body with a hardness difference between the surface and inside is achieved by controlling the monoclinic crystal ratio and lattice structure, where the surface has low hardness for easy processing and the inside has high hardness for durability, using specific stabilizing elements and germanium oxide content.

Benefits of technology

The solution provides a zirconia sintered body with enhanced workability due to low surface hardness for easy processing and high inner hardness for improved scratch resistance and wear resistance, overcoming the trade-off between these properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025010099000001_ABST
    Figure 2025010099000001_ABST
Patent Text Reader

Abstract

To provide at least one of a zirconia sintered body having a hardness difference between the surface of the sintered body and the interior of the sintered body, the surface of the sintered body having high workability and the interior of the sintered body having high hardness, raw materials for obtaining the sintered body and a method for manufacturing the sintered body.SOLUTION: The present invention relates to a zirconia sintered body containing more than 0% but less than 2.0 mol% of a stabilizing element. When a monoclinic crystal ratio in the burned surface of the sintered compact is Fm,a, and the monoclinic crystal ratio in the central part of the sintered body is Fm,p, Fm,a is 50% or greater and Fm,a>Fm,p.SELECTED DRAWING: Figure 6
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a zirconia sintered body having a difference in hardness between the surface and the interior of the sintered body, and a method for producing the same. [Background technology]

[0002] Zirconia-based sintered bodies have characteristics such as high strength and high toughness, and are therefore widely used as grinding media, structural materials, decorative parts, bio-related materials, etc. In particular, sintered bodies used for decorative parts of watches, portable electronic devices, automobiles, home appliances, etc., desirably have high hardness from the viewpoints of scratch resistance and wear resistance in addition to high strength and high toughness.

[0003] For example, Patent Document 1 reports a zirconia-alumina composite sintered body obtained by mixing and sintering Ce-stabilized zirconia powder, Y-stabilized zirconia powder, zinc oxide powder, and alumina powder. It is described that the sintered body has high strength and toughness, as well as high hardness with a Vickers hardness of 1601 to 1843.

[0004] Incidentally, zirconia sintered bodies are almost always subjected to processing such as grinding and polishing to remove the sintered surface (the surface of the sintered body immediately after sintering). The sintered surface is rough and has many irregularities (hereinafter also referred to as "fracture sources") that can be the starting point of fracture of the sintered body. Therefore, sintered bodies with the sintered surface remaining have low strength against load. Therefore, before evaluating the sintered body or using it for various purposes, it is necessary to remove the sintered surface by grinding or polishing. However, when the sintered body has a high hardness, it has poor machinability and is difficult to process. Therefore, sintered bodies with excellent processability that have been reduced in hardness to improve machinability have also been reported.

[0005] For example, Patent Document 2 reports an easily workable sintered body obtained by mixing Nb2O5, Y2O3, and zirconia, adding TiO2 as necessary, and sintering the mixture. It also describes that the Vickers hardness of the sintered body is not too high, at 8.76 to 8.79 GPa, and that it can be worked using a diamond drill for cutting. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2006-056746 A [Patent Document 2] JP 2015-127294 A Summary of the Invention [Problem to be solved by the invention]

[0007] There is a trade-off between the hardness and workability of a sintered body. While a sintered body with high hardness is required from the viewpoint of scratch resistance and abrasion resistance, a sintered body with low hardness is required from the viewpoint of workability.

[0008] An object of the present disclosure is to provide a zirconia sintered body having a hardness difference between the surface and the inside of the sintered body, the surface of the sintered body having a low hardness and high workability, and the inside of the sintered body having a high hardness, as well as at least one of a raw material for obtaining the sintered body and a method for manufacturing the sintered body. [Means for solving the problem]

[0009] That is, the present invention is as defined in the claims, and the gist of the present disclosure is as follows. [1] A zirconia sintered body containing a stabilizing element in an amount of more than 0 mol% and less than 2.0 mol%, and the monoclinic ratio in the sintered surface of the sintered body is F m,a , the monoclinic ratio in the center of the sintered body is F m,p Then, F m,a is 50% or more and F m,a >F m,pZirconia sintered body [2] A zirconia sintered body containing more than 0 mol% and less than 2.0 mol% of a stabilizing element, in which in an XRD pattern at the center of the sintered body, the difference in 2θ of the peak top corresponding to the (400) plane of tetragonal zirconia from the 2θ of the peak top corresponding to the (004) plane of tetragonal zirconia is 1.5° or more. [3] The zirconia sintered body according to [1], wherein the stabilizing element is one or more elements selected from the group consisting of yttrium, calcium, magnesium and lanthanides. [4] The zirconia sintered body according to [1] or [2], which contains germanium oxide. [5] The zirconia sintered body according to [3], having a germanium oxide content of more than 0% and less than 8.0 mol%. [6] The zirconia sintered body according to any one of [1] to [4], which contains alumina. [7] A zirconia sintered body according to any one of [1] to [5], having a hardness improvement rate before and after polishing of 3% or more. [8] A method for producing a zirconia sintered body according to any one of [1] to [8] above, comprising a step of sintering a powder containing zirconia containing a stabilizing element and germanium oxide, the zirconia having a monoclinic rate of more than 80%, and having a G / S ratio of 0.35 or more when the amount of the stabilizing element in the powder is S mol % and the amount of germanium oxide is G mol %, in an air atmosphere at 1100°C to 1500°C for 0.3 hours to 20 hours. [9] A powder comprising zirconia containing a stabilizing element and germanium oxide, wherein the zirconia has a monoclinic rate of more than 80% and, when the amount of the stabilizing element in the powder is S mol% and the amount of germanium oxide is G mol%, the G / S ratio is 0.35 or more.

[10] A method for producing a zirconia sintered body using the powder described in [9] above.

[11] A member comprising the sintered body according to any one of [1] to [7]. Effect of the Invention

[0010] The present disclosure makes it possible to provide a zirconia sintered body having a hardness difference between the surface and the inside of the sintered body, the surface of the sintered body being highly workable and the inside of the sintered body being highly hard, as well as at least one of a raw material for obtaining the sintered body and a method for producing the sintered body. [Brief description of the drawings]

[0011] [Figure 1] Schematic diagram of a cross section of zirconia sintered body [Diagram 2] Schematic diagram of Vickers indentation after Vickers hardness test [Diagram 3] XRD patterns of the scorched surface and center of Example 6 [Figure 4] Appearance of Vickers indentation on the hardened and polished surfaces of Example 6 after Vickers hardness measurement [Diagram 5] Appearance of the sintered bodies of Example 6 and Comparative Example 6 [Figure 6] Cross-sectional SEM image of the sintered surface and center of Example 12 (magnification: 2000 times) [Figure 7] XRD patterns at the center of Example 12 and Comparative Example 5 DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The sintered body of the present disclosure will be described below by showing an example of an embodiment. In addition, the configurations and parameters disclosed in this specification can be arbitrarily combined, and the upper and lower limits of the values ​​disclosed in this specification can be arbitrarily combined. Each term in this embodiment is as follows.

[0013] The "sintered surface" refers to the surface of a sintered body immediately after sintering. In other words, it means the surface of a sintered body that has not been processed or treated after sintering. The surface of such a sintered body is rough, and the surface roughness Ra is greater than 0.04 μm, and the surface roughness Ra is greater than 0.04 μm and is equal to or less than 0.1 μm.

[0014] The "depth direction" refers to a direction perpendicular to a point on the surface of the sintered body toward the inside of the sintered body.

[0015] The "sintered surface" is a portion of a sintered body immediately after sintering, which has a certain depth from the surface of the sintered body (i.e., the sintered surface) toward the inside of the sintered body, where a part of the crystal phase changes from the tetragonal phase to the monoclinic phase, and which contains the tetragonal phase and a considerable amount of the monoclinic phase. In this embodiment, the portion 10 μm deep from the sintered surface of the sintered body is considered to be the sintered surface.

[0016] The method of processing the burnt surface to remove the destruction source (burnt surface) on the surface of the sintered body is arbitrary, but it is preferable to use a surface grinder to grind 10 μm or more in the depth direction. This makes it possible to remove the burnt surface and even the burnt surface. For example, grinding 50 μm or more, 0.1 mm or 0.3 mm or more in the depth direction can be mentioned, and grinding 0.5 mm or less in the depth direction can be mentioned.

[0017] The "center" of a sintered body refers to the part that is deeper than 10 μm from the surface (burned surface) of the sintered body. The part up to 10 μm in the depth direction from the surface (burned surface) of the sintered body is the burned surface. The part exceeding 10 μm in the depth direction is the center. Therefore, by processing the surface of the sintered body more than 10 μm in the depth direction, it is possible to expose the center at the surface of the sintered body.

[0018] The "polished surface" refers to a smooth sintered body surface, with a surface roughness Ra of 0.04 μm or less. For example, the polishing method may involve removing the burnt surface by the above-mentioned method, followed by mirror polishing with an abrasive cloth, polishing with a diamond slurry with an average particle size of 3 μm, and polishing with colloidal silica of 0.03 μm in that order. The polished surface in this embodiment is preferably the surface at the center, and is preferably a surface in which the sintered body surface (burnt surface) is removed by 10 μm or more in the depth direction, and the surface roughness Ra of the polished sintered body is 0.04 μm or less.

[0019] FIG. 1 shows a cross section of a zirconia sintered body (100) with its top surface polished, and consists of a central part (13) and a sintered surface (14). In FIG. 1, the sintered body surface (11) is the "polished surface", which is the surface of the sintered body after polishing. The polished surface (11) is also the surface of the central part (13) exposed on the surface of the sintered body by processing the surface after sintering, such as polishing, by 10 μm or more. The sintered body surface (12) is the "sintered surface", which is the surface of the sintered body after sintering, and is the surface of the sintered surface (14). The depth direction (15) is the direction perpendicular to the interior of the sintered body from any point on the sintered body surfaces (11, 12), as shown by the arrows in the figure.

[0020] The "monoclinic crystal ratio" is the ratio of monoclinic zirconia to the zirconia crystal phase. The monoclinic crystal ratio can be calculated from the X-ray diffraction (hereinafter also referred to as XRD) pattern by the following formula. The monoclinic crystal ratio F of the sintered body's sintered surface is m,a When calculating the monoclinic crystal ratio F(%), use the XRD pattern on the sintered surface and the monoclinic crystal ratio F(%) at the center of the sintered body. m,p When determining the monoclinic crystal ratio (%), the XRD pattern at the center is used, and when determining the monoclinic crystal ratio of the powder, the XRD pattern of the powder is used.

[0021] F m ={I m (111)+I m (11-1)} / [I m (111)+I m (11-1)+I t,c (111)]×100 (1) In formula (1), F m is the monoclinic ratio (%), I m (111) and I m (11-1) are the area intensities of the XRD peaks corresponding to the monoclinic (111) and (11-1) planes, respectively, and I t,c (111) is the sum of the area intensity of the XRD peak corresponding to the (111) plane of the tetragonal crystal and the area intensity of the XRD peak corresponding to the (111) plane of the cubic crystal. Therefore, the monoclinic crystal ratio is calculated as an area ratio.

[0022] In this embodiment, the X-ray diffraction patterns of the sintered body and powder can be measured by a general X-ray diffraction device for crystallinity analysis (for example, device name: Ultima IV, manufactured by RIGAKU Corporation).

[0023] The measurement conditions are as follows:

[0024] Radiation source: CuKα radiation (λ=1.5418Å) Tube voltage: 45kV Tube current: 40mA Measurement mode: Continuous scan Scan speed: 4° / min Step width: 0.02° Measurement range: 2θ=26° to 33° Goniometer: Radius 185mm In the above-mentioned XRD pattern measurement, the XRD peaks corresponding to the respective crystal planes of zirconia in this embodiment are measured as peaks having peak tops at the following 2θ.

[0025] XRD peak corresponding to the (111) plane of monoclinic zirconia: 2θ=31±0.5° XRD peak corresponding to the (11-1) plane of monoclinic zirconia: 2θ=28±0.5° The XRD peaks corresponding to the (111) planes of tetragonal zirconia and cubic zirconia were measured in duplicate, and the 2θ angle of the peak top was 2θ=30±0.5°.

[0026] The patterns obtained by the above-mentioned XRD pattern measurement can be analyzed using the integrated powder X-ray analysis software "PDXL".

[0027] "2θ (400)t-(004)t " is the difference in 2θ of the peak top corresponding to the (400) plane of tetragonal zirconia in the XRD pattern at the center of the sintered body from the 2θ of the peak top corresponding to the (004) plane of tetragonal zirconia.

[0028] In this embodiment, the X-ray diffraction pattern including peaks corresponding to the tetragonal (004) and (400) planes of the zirconia sintered body can be measured using a general X-ray diffraction device (for example, device name: Ultima IV, manufactured by RIGAKU Corporation).

[0029] The measurement conditions are as follows:

[0030] Radiation source: CuKα radiation (λ=1.5418Å) Tube voltage: 45kV Tube current: 40mA Measurement mode: Continuous scan Scan speed: 2° / min Step width: 0.02° Measurement range: 2θ=72° to 76° Goniometer: Radius 185mm In the above-mentioned XRD pattern measurement, the XRD peaks corresponding to each crystal plane of zirconia contained in the central part of the zirconia sintered body of this embodiment are measured as peaks having peak tops at the following 2θ.

[0031] XRD peak corresponding to the (004) plane of tetragonal zirconia: 2θ=72.5±0.5° XRD peak corresponding to the (400) plane of tetragonal zirconia: 2θ=74.5±0.5° The pattern obtained by the above-mentioned XRD pattern measurement can be analyzed using the integrated powder X-ray analysis software "PDXL". Specifically, the "PDXL" program can be used to remove the background and the XRD peak due to CuKα2 radiation (λ=1.5443 Å).

[0032] A schematic diagram of the Vickers indentation after a Vickers hardness test is shown in Figure 2. The Vickers hardness can be calculated from the Vickers indentation obtained under the above-mentioned conditions using the following formula.

[0033] HV=0.1891×F / {(a1+a2) / 2} 2 (2) In formula (2), HV is the Vickers hardness, F is the measurement load (N), and a1 and a2 are the diagonal lengths of the indentation (mm).

[0034] (Sintered body) Hereinafter, the zirconia sintered body of this embodiment will be described.

[0035] The zirconia sintered body of the present embodiment is a zirconia sintered body containing more than 0 mol% and less than 2.0 mol% of a stabilizing element, and the monoclinic ratio in the sintered surface of the sintered body is F m,a , the monoclinic ratio in the center of the sintered body is F m,p Then, F m,a is 50% or more and F m,a >F m,p The zirconia sintered body is

[0036] The zirconia sintered body of the present embodiment has a monoclinic ratio F m,a The annealed surface has a monoclinic crystal ratio of 50% or more. m,p The zirconia sintered body of this embodiment has a sintered surface having a monoclinic ratio of 50% or more on the surface and a central portion located 10 μm or more inside the sintered surface. The sintered surface of the zirconia sintered body of this embodiment can be easily processed, and the wear of the cutting tool can be reduced. The zirconia sintered body of this embodiment is a sintered body including a sintered surface having a monoclinic ratio of 50% or more on the surface after sintering (as-is), and a central portion located inside the sintered surface and having a monoclinic ratio of less than 50%, but this embodiment is not limited thereto. As another embodiment, a sintered body in which the monoclinic ratio of only the surface layer is 50% or more by processing or treatment other than sintering is also included in the present disclosure, and has the same effect as the zirconia sintered body of this embodiment.

[0037] The monoclinic ratio (F m,a The monoclinic ratio F at the center of the zirconia sintered body of the present embodiment is 50% or more, preferably 70% or more or 80% or more, and may be 100% or less or less than 100%, and is preferably 50% or more and 100% or less, or 80% or more and 100% or less. m,pis smaller than the monoclinic ratio of the sintered surface, and is preferably less than 50%, and more preferably less than 30% or less than 10%. m,a is measured by the above-mentioned XRD pattern measurement on the surface of the sintered body that has been polished 3 μm in the depth direction. Note that the zirconia crystal phase in the center is assumed to remain unchanged before and after processing.

[0038] Monoclinic ratio F m,p may be 0% or more or 1% or more, and is preferably 0% or more and less than 50%, or 1% or more and less than 10%.

[0039] In addition, the central portion of the zirconia sintered body of the present embodiment has a 2θ (400)t-(004)t is preferably 1.5° or more. This makes it easier to improve the hardness of the center portion.

[0040] 2θ (400)t-(004)t is preferably 1.5° or more, 1.6° or more, or 1.7° or more. (400)t-(004)t When 2θ is 1.7° or more, the monoclinic ratio is likely to be small. (400)t-(004)t When the 2θ angle is 1.73° or more, and further when the 2θ angle is 1.75° or more, the resistance to hydrothermal degradation tends to be high. (400)t-(004)t is preferably 3.0° or less, 2.5° or less, 2.2° or less, or 2.0° or less, and more preferably 1.5° or more and 3.0° or less, 1.6° or more and 2.5° or less, 1.7° or more and 2.0° or less, or 1.73° or more and 2.0° or less.

[0041] In addition, the central portion of the zirconia sintered body of this embodiment preferably has an axial ratio c / a of 1.018 or more, calculated from the lattice constant calculated from 2θ of the peaks corresponding to the tetragonal (004) and (400) planes. This makes it easier to improve the hardness of the central portion. c / a is preferably 1.018 or more, or 1.020 or more, and may be 1.025 or less, or 1.023 or less.

[0042] The structure of the zirconia sintered body of this embodiment may be a structure having a sintered surface, a sintered surface, a center portion, a sintered surface, and a sintered surface in this order from one surface of the sintered body to the opposing surface. Also, the sintered surface and the sintered surface may be removed, and the structure may consist of only the center portion.

[0043] The zirconia sintered body of the present embodiment is a sintered body containing zirconia containing a stabilizing element, and is a sintered body having zirconia containing a stabilizing element as a main phase, that is, a so-called zirconia sintered body.

[0044] The stabilizing element may be any element that has a function of stabilizing zirconia, and is preferably one or more selected from the group consisting of calcium (Ca), magnesium (Mg), scandium (Sc), yttrium (Y), cerium (Ce), gadolinium (Gd) and ytterbium (Yb), and is preferably at least one of yttrium and gadolinium, more preferably yttrium. The sintered body in this embodiment may contain two or more kinds of the stabilizing elements.

[0045] The content of the stabilizing element (hereinafter also referred to as "amount of stabilizing element", and when the stabilizing element is yttrium, etc., also referred to as "amount of yttrium") may be an amount that partially stabilizes zirconia. The amount of the stabilizing element is, in terms of oxide, more than 0 mol%, 0.25 mol% or more, or 0.5 mol% or more, and may be less than 2.0 mol%, 1.8 mol% or less, or 1.5 mol% or less, and is preferably more than 0 mol% and less than 2.0 mol%, more than 0 mol% and 1.8 mol% or less, or 0.5 mol% or more and 1.5 mol% or less. In this embodiment, the amount of the stabilizing element is the ratio (mol%) of the total amount of the stabilizing element calculated as an oxide to the total amount of zirconia and the stabilizing element calculated as an oxide.

[0046] The zirconia sintered body of this embodiment may not contain germanium oxide, but preferably contains germanium oxide. Germanium oxide (GeO2) may not be dissolved in zirconia, or may be at least partially dissolved in zirconia. The amount of germanium oxide is 0 mol% or more, 0.5 mol% or more, or 1.0 mol% or more, and may be less than 8.0 mol%, less than 7.5 mol%, or less than 5.0 mol%, in terms of oxide. Furthermore, 0 mol% or more and less than 8.0 mol%, more than 0 mol% and less than 7.5 mol%, or 0.5 mol% or more and less than 5.0 mol% are preferable. In this embodiment, the amount of germanium oxide is the ratio (mol%) of the total of germanium oxide to the total of zirconia, the stabilizing element converted into oxide, and germanium oxide.

[0047] The zirconia sintered body of this embodiment may contain alumina (Al2O3). Since the zirconia sintered body of this embodiment may not contain alumina, the alumina content is 0 mass% or more. When alumina is contained, the alumina content may be more than 0 mass% and less than 30 mass%, preferably more than 0 mass% and 25 mass% or less, more preferably 0.005 mass% or more and 20 mass% or less. The alumina content may be 0 mass% or more, more than 0 mass%, 0.005 mass% or more, 0.05 mass% or more, or 0.25 mass% or more, and may be 30 mass% or less, 25 mass% or less, 20 mass% or less, 1 mass% or less, or 0.5 mass% or less. From the viewpoint that the zirconia sintered body of this embodiment can easily obtain translucency and has excellent processability, it is preferable that the alumina content is not contained. On the other hand, from the viewpoint that a dense sintered body is easily obtained even at a relatively low temperature, the alumina content is preferably 0.01 mass% or more. In addition, since the mechanical properties of the zirconia sintered body of this embodiment, such as static strength, tend to be high, the alumina content is preferably 30 mass% or less. When the zirconia sintered body of this embodiment contains germanium oxide and alumina, the alumina content is the mass ratio of aluminum converted into Al2O3 to the total amount of zirconia, stabilizing elements converted into oxides, germanium oxide, and aluminum converted into Al2O3.

[0048] The zirconia sintered body of this embodiment may contain a pigment component. The pigment component contained in the sintered body refers to a component that has the function of coloring the sintered body. This allows the sintered body to exhibit any color tone different from the original color tone of zirconia. The pigment component contained in the zirconia sintered body of this embodiment is at least one of an element and its compound that has the function of coloring zirconia, and is preferably, for example, a compound containing a metal element, and further a transition metal element and a compound containing the same. As a specific pigment component, it is more preferable that it is one or more elements selected from the group consisting of vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu) and zinc (Zn), and a compound containing one or more of these, and it is even more preferable that it is an oxide containing one or more elements selected from the group consisting of manganese, iron, cobalt, nickel and zinc. As the pigment component, for example, by sintering a mixture of zirconia powder and pigment powder, a coloring element derived from the pigment powder or a compound containing the coloring element can be contained as a pigment component in the zirconia sintered body.

[0049] The pigment component in the zirconia sintered body of the present embodiment may have any form, and the pigment component may be contained as particles (second phase particles) or may be dissolved in zirconia.

[0050] The content of the pigment component of the zirconia sintered body of this embodiment is preferably 0% by mass or more, more than 0% by mass, 0.001% by mass or more, 0.005% by mass or more, 0.01% by mass or more, 0.05% by mass or more, or 0.1% by mass or more. The content of the pigment component is arbitrary, but the content of the pigment component may be, for example, 5.0% by mass or less, 3.5% by mass or less, or 3.0% by mass or less, and is preferably 0% by mass or more and 5.0% by mass or less, more than 0% by mass and 5.0% by mass or less, or 0.1% by mass or more and 3.0% by mass or less. The content of the pigment component can be determined as the ratio of the total mass of the pigment components converted into oxides to the mass of the zirconia sintered body of this embodiment. The pigment components may be converted into oxides as follows: cobalt is Co3O4, iron is Fe2O3, manganese is MnO2, and zinc is ZnO. Furthermore, when the zirconia sintered body of the present embodiment contains germanium oxide, alumina, and a pigment component, and the pigment component forms a composite oxide, the content of the pigment component can be determined as the ratio of the mass of the pigment component converted into a composite oxide to the total amount of zirconia, the stabilizing element converted into an oxide, germanium oxide, aluminum converted into Al2O3, and the pigment component converted into a composite oxide.

[0051] The zirconia sintered body of the present embodiment may contain at least one additive selected from the group consisting of silica (SiO2), titania (TiO2), gallium oxide (Ga2O3), niobium oxide (Nb2O5) and tantalum oxide (Ta2O5) in addition to germanium oxide, alumina and pigment components. By containing such additives, a sintered body having desired mechanical properties can be obtained.

[0052] The zirconia sintered body of this embodiment may contain inevitable impurities such as hafnia (HfO2), but it is preferable that it does not contain anything other than stabilizing elements, zirconia, alumina, pigment components as necessary, and inevitable impurities. In this embodiment, the content of each component of the sintered body may be calculated by regarding hafnia (HfO2) as zirconia (ZrO2).

[0053] For example, when the zirconia sintered body of the present embodiment is a zirconia sintered body containing a composite oxide represented by ABO3 or AB2O4, germanium oxide, alumina, and silica as pigment components, and also containing gadolinium and yttrium as stabilizing elements, the content of each component may be determined as follows.

[0054] Pigment content [mass%] = {(ABO2+AB2O4) / (Gd2O3+Y2O3+ZrO2 +GeO2+Al2O3+SiO2+ABO3+AB2O4)}×100 Alumina content [mass%] = {Al2O3 / (Gd2O3+Y2O3+ZrO2 +GeO2+Al2O3+SiO2+ABO3+AB2O4)}×100 Silica content [mass%] = {SiO2 / (Gd2O3+Y2O3+ZrO2 +GeO2+Al2O3+SiO2+ABO3+AB2O4)}×100 Amount of germanium oxide [mol%] = {GeO2 / (GeO2+Gd2O3+Y2O3+ZrO2)}×100 Stabilizing element amount [mol%]={(Gd2O3+Y2O3) / (Gd2O3+Y2O3+ZrO2)}×100 Gadolinium content [mol%] = {(Gd2O3) / (Gd2O3+Y2O3+ZrO2)}×100 Amount of yttrium [mol%] = {(Y2O3) / (Gd2O3+Y2O3+ZrO2)}×100 The zirconia sintered body of the present embodiment preferably has a high density, and the relative density is more preferably 98% or more, and further preferably 99% or more and 100% or less.

[0055] In this embodiment, the relative density can be calculated from the ratio of the measured density to the true density. The measured density is the mass measured by mass measurement relative to the volume measured by the method specified in JIS R 1634 (the so-called Archimedes method).

[0056] The true density ρ of the sintered body in this embodiment th (g / cm 3 ) can be calculated from the following formula when the content (mol%) of the oxide of the stabilizing element contained in the sintered body is X when no additives or pigment components are contained.

[0057] ρ Zr =[124.25(100-X)+MsX] / α 2 β[150.5(100+X)] Here, ρ Zr is the true density of zirconia, and α and β are the following values.

[0058] α=0.5080+0.06980X / (100+X) β=0.5195-0.06180X / (100+X) Ms is the molar mass (g / mol) of the oxide of the stabilizing element. For example, if the stabilizing element is yttrium, Ms = 225.81.

[0059] In addition, when the sintered body of this embodiment contains additives including germanium oxide and alumina oxide, and other pigment components, the true density of the sintered body is calculated by the above-mentioned method using the true density ρ Zr The true density of the sintered body can be calculated using the true density of the additives and pigment components shown below. In other words, the true density of the sintered body is the reciprocal of the mass percentage of each component contained in the sintered body divided by the true density of each component and added together. For example, in the case of a sintered body containing Y mass% germanium oxide and Z mass% alumina oxide, the true density ρ th can be calculated as follows:

[0060] ρ th =100 / [(Y / 4.25)+(Z / 3.987)+(100―Y―Z) / ρ Zr ] The true densities of the additives and pigment components may be as follows:

[0061] Germanium oxide (GeO2): 4.25 [g / cm 3 ] Alumina (Al2O3): 3.987 [g / cm 3 ] In addition, the above formula does not take into account the solid solution of the additives germanium oxide and alumina oxide in the zirconia part, so the true density ρ th may be smaller than the actual density, and the relative density may exceed 100%. In that case, the relative density is considered to be "100%".

[0062] In this embodiment, the sintered body preferably has a low Vickers hardness at the sintered surface. On the other hand, the central part of the sintered body preferably has a high Vickers hardness. The Vickers hardness is measured by a Vickers hardness test according to JIS R1610:2003, and the following conditions can be exemplified as the measurement conditions.

[0063] Sample thickness: 1.5±0.5mm Measurement load: 5kgf In the zirconia sintered body of this embodiment, the hardness of the burned surface is preferably lower, for example, less than 1400HV, and preferably less than 1300HV or less than 1200HV. The lower the hardness of the burned surface, the easier it is to remove the burned surface by grinding. On the other hand, the higher the hardness of the center portion, the more preferable, and preferably 1000HV or more, 1050HV or more, or 1100HV or more. The higher the hardness of the center portion of the sintered body, the less likely the surface is to be scratched during use in various applications, and the more improved the scratch resistance.

[0064] In the zirconia sintered body of this embodiment, the Vickers hardness of the center is preferably higher than that of the burnt surface. This makes it possible to provide a sintered body with high scratch resistance while facilitating grinding of the burnt surface. In this embodiment, the hardness increase rate before and after polishing of the burnt surface of the sintered body (hereinafter also simply referred to as the "hardness increase rate") is preferably greater than 0%, more preferably 3% or more, 5% or more, or 10% or more. The hardness increase rate can be 50% or less or 30% or less, and can be exemplified as more than 0% and 50% or less, 3% or more and 50% or less, or 10% or more and 50% or less. The hardness increase rate represents the ratio of the hardness of the center to the hardness of the burnt surface of the sintered body, and is calculated by the following formula.

[0065] Hardness increase rate (%) = (Vickers hardness at center - Vickers hardness at hardened surface) / Vickers hardness of burnt surface x 100 The shape of the zirconia sintered body of the present embodiment may be, for example, one or more selected from the group consisting of a sphere, an approximately sphere, an ellipse, a disk, a cylinder, a cube, a rectangular parallelepiped, a polyhedron, and an approximately polyhedron. Furthermore, any shape may be used to achieve the intended purpose, such as various applications.

[0066] The zirconia sintered body of the present embodiment can be applied to the applications of conventional sintered bodies, particularly zirconia sintered bodies such as structural materials, optical materials, and dental materials, but can also be used as components that require advanced processing, such as decorative items, covers for accessories such as watches and housings, and exterior components for portable electronic devices such as mobile phones. (Zirconia sintered body after processing) The zirconia sintered body of the present embodiment may have the sintered surface removed by any processing method. The zirconia sintered body after processing in which the sintered surface is removed and only the center portion remains (hereinafter, also simply referred to as the "processed zirconia sintered body") has high hardness and high scratch resistance, and therefore, when applied to applications such as the above-mentioned decorative articles, cover members, and exterior members, the aesthetics are improved.

[0067] The zirconia sintered body after processing preferably has a surface roughness Ra of 0.04 μm or less. Since the source of fracture on the surface of the sintered body is removed, the strength against fracture is improved.

[0068] The zirconia sintered body of this embodiment may be regarded as having the same composition in both the sintered surface and the central portion. That is, the composition of the zirconia sintered body after processing may be regarded as being the same as the composition of the zirconia sintered body of this embodiment before processing described above. For example, the zirconia sintered body after processing may contain yttrium in an amount of more than 0 mol% and less than 2.0 mol% as a stabilizing element, germanium oxide in an amount of more than 0 mol% and less than 8.0 mol%, and may contain additive components such as pigment components and alumina.

[0069] The processed zirconia sintered body is composed of only the above-mentioned central part. That is, the processed zirconia sintered body has a 2θ (400)t-(004)t is 1.5° or more.

[0070] The processed zirconia sintered body preferably has an axial ratio c / a of 1.018 or more, calculated from the lattice constant calculated from 2θ of the peaks corresponding to the tetragonal (004) plane and (400) plane.

[0071] In addition, various characteristics and physical properties, such as the hardness and XRD pattern of the processed zirconia sintered body, are the same as those of the central part of the zirconia sintered body of this embodiment. (powder) The powder of this embodiment contains zirconia containing a stabilizing element and germanium oxide, and the zirconia has a monoclinic rate of more than 80%. When the amount of the stabilizing element in the powder is S mol % and the amount of germanium oxide is G mol %, the powder has a G / S of 0.35 or more.

[0072] The zirconia contained in the powder of this embodiment contains a stabilizing element. The stabilizing element is at least one selected from the group consisting of calcium, magnesium, scandium, yttrium, cerium, gadolinium, and ytterbium, and is preferably at least one of yttrium and gadolinium, and more preferably yttrium. The zirconia contained in the powder of this embodiment may contain two or more of the stabilizing elements.

[0073] The amount of the stabilizing element in the powder of this embodiment may be the same as that of the target sintered body. The amount of the stabilizing element, calculated as oxide, may be more than 0 mol%, 0.25 mol% or more, or 0.5 mol% or more, and may be less than 2 mol%, 1.8 mol% or less, or 1.5 mol% or less. More preferably, the amount is more than 0 mol% and less than 2 mol%, more than 0 mol% and 1.8 mol% or less, or 0.5 mol% or more and 1.5 mol% or less.

[0074] The stabilizing element is preferably present as a solid solution in zirconia, and the powder of this embodiment preferably does not contain any undissolved stabilizing element.

[0075] The powder of this embodiment has a G / S of 0.35 or more, preferably 0.5 or more, 1.0 or more, 1.5 or more, or 2.0 or more. G / S can be 10.0 or less, 8.0 or less, or 5.0 or less, and is preferably 0.35 or more and 10.0 or less, 0.5 or more and 8.0 or less, or 1.0 or more and 5.0 or less.

[0076] The powder of this embodiment may contain alumina (Al2O3). Since the powder of this embodiment may not contain alumina, the alumina content is 0 mass% or more. When alumina is contained, the alumina content may be more than 0 mass% and less than 30 mass%, preferably more than 0 mass% and 25 mass% or less, more preferably 0.005 mass% or more and 20 mass% or less. The alumina content may be 0 mass% or more, more than 0 mass%, 0.005 mass% or more, 0.05 mass% or more, or 0.25 mass% or more, and may be 30 mass% or less, 25 mass% or less, or 20 mass% or less. It is preferable that the alumina is not contained from the viewpoint that the obtained zirconia sintered body can easily obtain translucency and can have excellent processability. On the other hand, from the viewpoint that a dense sintered body is easily obtained even at a relatively low temperature, the alumina content is preferably 0.01 mass% or more, and the mechanical properties of the obtained zirconia sintered body, such as mechanical properties such as static strength, tend to be high, so that the alumina content is preferably 30 mass% or less. When the powder of this embodiment contains germanium oxide and alumina, the alumina content is the mass ratio of aluminum calculated as Al2O3 to the total amount of zirconia, stabilizing elements calculated as oxides, germanium oxide, and aluminum calculated as Al2O3.

[0077] The powder of this embodiment may contain a pigment. This allows the resulting sintered body to exhibit a color tone different from the original color tone of zirconia. The pigment contained in the powder of this embodiment is at least one of an element having a function of coloring zirconia and a compound thereof, and is preferably, for example, a compound containing a metal element, and further preferably a compound containing a transition metal element. As a specific pigment, it is more preferable that it is a compound containing one or more elements selected from the group consisting of vanadium, chromium, manganese, iron, cobalt, nickel, copper, and zinc, and it is even more preferable that it is an oxide containing one or more elements selected from the group consisting of manganese, iron, cobalt, nickel, and zinc.

[0078] Since the powder of this embodiment does not need to contain a pigment, the pigment content is 0% by mass or more. When a pigment is contained, the pigment content is more than 0% by mass, preferably 0.001% by mass or more, 0.005% by mass or more, 0.01% by mass or more, 0.05% by mass or more, or 0.1% by mass or more, and preferably 5.0% by mass or less or 3.5% by mass or less. The pigment content can be calculated as the ratio of the total mass of the pigment, calculated as an oxide, to the mass of the powder of this embodiment, calculated as an oxide. In addition, when the pigment component forms a composite oxide, the pigment content can be calculated as the ratio of the total mass of the pigment component, calculated as a composite oxide, to the mass of the zirconia sintered body of this embodiment.

[0079] The powder of this embodiment may contain, in addition to germanium oxide, alumina, and pigment, one or more additives selected from the group consisting of silica (SiO2), titania (TiO2), gallium oxide (Ga2O3), niobium oxide (Nb2O5), and tantalum oxide (Ta2O5). By containing the additives, a sintered body having desired mechanical properties can be obtained.

[0080] The powder of this embodiment may contain inevitable impurities such as hafnia (HfO2). However, it is preferable that the powder does not contain anything other than stabilizing elements, zirconia, alumina, pigments as necessary, and inevitable impurities. In this embodiment, the content of each component in the powder may be calculated by regarding hafnia (HfO2) as zirconia (ZrO2).

[0081] For example, when the powder of this embodiment is a powder of zirconia containing a composite oxide represented by ABO3 or AB2O4, germanium oxide, alumina, and silica as pigments, and also containing gadolinium and yttrium as stabilizing elements, the content of each component may be determined as follows.

[0082] Pigment amount [mass%] = {(ABO2+AB2O4) / (Gd2O3+Y2O3+ZrO2 +GeO2+Al2O3+SiO2+ABO3+AB2O4)}×100 Alumina content [mass%] = {Al2O3 / (Gd2O3+Y2O3+ZrO2 +GeO2+Al2O3+SiO2+ABO3+AB2O4)}×100 Silica content [mass%] = {SiO2 / (Gd2O3+Y2O3+ZrO2 +GeO2+Al2O3+SiO2+ABO3+AB2O4)}×100 Amount of germanium oxide [mol%] = {GeO2 / (GeO2+Gd2O3+Y2O3+ZrO2)}×100 Stabilizing element amount [mol%]={(Gd2O3+Y2O3) / (Gd2O3+Y2O3+ZrO2)}×100 Gadolinium content [mol%] = {(Gd2O3) / (Gd2O3+Y2O3+ZrO2)}×100 Amount of yttrium [mol%] = {(Y2O3) / (Gd2O3+Y2O3+ZrO2)}×100 The monoclinic ratio of the zirconia contained in the powder of this embodiment is more than 80%, and is preferably 85% or more or 90% or more. The monoclinic ratio is 100% or less, and when the zirconia contains at least one of tetragonal and cubic crystals, the monoclinic ratio is less than 100%. The sum of the tetragonal ratio and the cubic ratio is preferably less than 20%, 15% or less, and more preferably 10% or less. The sum of the tetragonal ratio and the cubic ratio may be 0% or more, and tetragonal and cubic crystals may not be included.

[0083] The BET specific surface area of ​​the powder of this embodiment is 5 m 2 / g or more, 10m 2 / g or more or 15m 2 / g or more, and 2 / g, less than 35m 2 / g or less or 30m 2 / g or less, and 5m 2 / g or more 40m 2 / g, less than 10m 2 / g or more 35m 2 / g or less, or 15m 2 / g or more 30m 2 / g or less. BET specific surface roughness is preferably 5m 2 / g or more, it is possible to obtain a dense sintered body even at a relatively low sintering temperature. 2 If the powder has a particle size of less than 1 / g, the powder tends to have poor flowability.

[0084] The powder of this embodiment preferably has high moldability. Specifically, when the powder of this embodiment is uniaxially press-molded at a pressure of 50±5 MPa and then treated with cold isostatic pressing (hereinafter also referred to as "CIP") at a pressure of 196±5 MPa to form a molded body, the relative density of the molded body (hereinafter also referred to as "molded body density") is 49% or more or 50% or more, and 56% or less or 54% or less, and is preferably 49% or more and 56% or less, or 50% or more and 54% or less.

[0085] The powder of this embodiment can be used as a precursor for a calcined body or a sintered body, and is suitable as a raw material powder for applications such as decorative items, covers for accessories such as watches and housings, and exterior components for portable electronic devices such as mobile phones.

[0086] When the powder of the present embodiment is to be made into a calcined body or a sintered body, it may be molded into a compact (compressed powder) prior to the calcination or sintering. The molding, calcination and sintering can all be carried out by known methods.

[0087] When the powder of this embodiment is formed into a molded body, molding may be performed by a known method, for example, one or more methods selected from the group consisting of uniaxial pressing, cold isostatic pressing, slip casting, and injection molding.

[0088] In order to improve the shape stability, the molded body may contain a binder. The binder may be any organic binder used in molding ceramics, and may be, for example, one or more selected from the group consisting of acrylic resin, polyolefin resin, wax, and plasticizer. The binder content may be, for example, 25% by volume or more and 65% by volume or less of the volume of the molded body. Alternatively, the binder may be more than 0% by mass and 10% by mass of 100% by mass of the molded body.

[0089] The shape of the molded body may be any shape depending on the purpose, taking into consideration shrinkage due to sintering, and examples thereof include at least one selected from the group consisting of spherical, approximately spherical, elliptical, disk-like, cylindrical, cubic, rectangular, polyhedral, and approximately polyhedral.

[0090] The calcination may be performed by heat treatment at a temperature lower than the sintering temperature of the powder, for example, in an air atmosphere at 600° C. or higher and lower than 1200° C. The sintering may be performed by one or more known methods selected from the group consisting of pressure sintering, vacuum sintering, and atmospheric sintering. As it is simple and easy to apply industrially, atmospheric sintering is preferred, and atmospheric sintering in an air atmosphere at 1150° C. or higher and 1550° C. or lower, preferably 1200° C. or higher and 1500° C. or lower, is more preferred.

[0091] (Method of manufacturing powder and sintered body) Hereinafter, the method for producing the zirconia sintered body of this embodiment will be described.

[0092] The zirconia sintered body of this embodiment may be produced by any method as long as it has the above-mentioned properties. An example of the method for producing the zirconia sintered body of this embodiment is a production method having a step of sintering a powder (hereinafter also referred to as a "raw material composition") containing a stabilizing element source and zirconia. The powder may be subjected to the above-mentioned step (hereinafter also referred to as a "sintering step") in any form, and for example, it may be subjected to sintering after being formed into a molded body (pressed powder).

[0093] A preferred production method includes a method for producing a sintered body, which includes a step of sintering a powder containing zirconia containing a stabilizing element and germanium oxide, in which the zirconia has a monoclinic rate of more than 80% and has a G / S of 0.35 or more, where the amount of the stabilizing element in the powder is S mol %, and the amount of germanium oxide is G mol %, in an air atmosphere at 1100° C. to 1500° C. for 0.3 hours to 20 hours.

[0094] The stabilizing element source may be at least one of an oxide of the stabilizing element and a compound containing the stabilizing element as a precursor thereof, and may be at least one selected from the group consisting of oxides, hydroxides, oxychlorides, chlorides, acetates, nitrates, and sulfates as precursors of the oxides of the stabilizing element, and is preferably at least one of chlorides and nitrates. (Hereinafter, the stabilizing element sources when the stabilizing element is yttrium or gadolinium are also referred to as "yttrium source" and "gadolinium source", respectively.) The content of the stabilizing element source in the raw material composition may be equal to the amount of the stabilizing element in the target sintered body.

[0095] The yttrium source may be at least one of yttria (yttrium oxide; Y2O3) and its precursor yttrium compound, and may be one or more selected from the group consisting of yttrium chloride, yttria, and yttrium carbonate, with yttrium chloride being preferred.

[0096] The gadolinium source may be at least one of gadolinia (gadolinium oxide) and a gadolinium compound which is a precursor thereof, and may include one or more selected from the group consisting of gadolinium chloride, gadolinium, and gadolinium carbonate, with gadolinium chloride being preferred.

[0097] The raw material composition may contain a germanium source. The germanium source may be at least one of germanium oxide and a compound serving as a precursor thereof, and may be one or more selected from the group consisting of germanium hydroxide, chloride, alkoxide, nitrate, and sulfate, which serve as precursors of germanium oxide, and is preferably one or more selected from the group consisting of germanium oxide and its precursors, chloride, and alkoxide. The content of the germanium source in the raw material composition may be the same as the germanium content of the target sintered body.

[0098] The raw material composition may contain an alumina source. The alumina source is at least one of alumina (Al2O3) and a compound containing aluminum (Al) as a precursor thereof, and includes at least one selected from the group consisting of aluminum chloride, aluminum sulfate, aluminum nitrate, aluminum hydroxide, alumina sol, and alumina, and is preferably alumina. The content of the alumina source in the raw material composition may be the same as the alumina content of the target sintered body.

[0099] The zirconia may be zirconium oxide (ZrO2), or may be zirconia containing a stabilizing element. Examples of zirconia containing a stabilizing element include yttrium-stabilized zirconia. When using zirconia containing a stabilizing element, any method may be used to make the zirconia contain the stabilizing element. For example, a hydrated zirconia sol is mixed with a stabilizing element source having a content equivalent to the desired stabilizing element, and the mixture is dried, calcined, and washed with water.

[0100] Furthermore, germanium oxide-containing stabilized zirconia containing germanium oxide and a stabilizing element may be used as the zirconia. Examples of germanium oxide-containing stabilized zirconia include germanium oxide-containing yttrium stabilized zirconia. When germanium oxide-containing stabilized zirconia is used, any method can be used to make zirconia contain germanium oxide. For example, a method of mixing a hydrated zirconia sol with a stabilizing element source and a germanium source, drying, calcining and washing with water, or a method of mixing a hydrated zirconia sol with a stabilizing element source, drying and calcining, and then mixing with a germanium source and calcining the mixture may be used.

[0101] Any mixing method may be used, and preferably at least one of dry mixing and wet mixing, more preferably wet mixing, and even more preferably wet mixing using a ball mill.

[0102] The method for producing a zirconia sintered body of the present embodiment may include a step of molding the raw material composition into a molded body (compressed powder) (hereinafter also referred to as a "molding step").

[0103] The molded body may be produced by any method, and examples of the method include mixing zirconia, a stabilizing element source, a germanium source, and, if necessary, an additive such as an alumina source, by any method, and molding the mixture.

[0104] In order to improve the shape stability, the molded body may contain a binder. The binder may be any organic binder used in molding ceramics, and may be, for example, one or more selected from the group consisting of acrylic resin, polyolefin resin, wax, and plasticizer. The binder content may be, for example, 25% by volume or more and 65% by volume or less in the volume of the molded body at room temperature. Alternatively, the binder may be, for example, more than 0% by mass and 10% by mass in 100% by mass of the molded body.

[0105] The shape of the molded body may be any shape depending on the purpose, taking into consideration shrinkage due to sintering, and examples thereof include at least one selected from the group consisting of spherical, approximately spherical, elliptical, disk-like, cylindrical, cubic, rectangular, polyhedral, and approximately polyhedral.

[0106] The molding method may be a known molding method capable of converting the mixed powder into a green compact, and is preferably at least one selected from the group consisting of uniaxial pressing, isostatic pressing, injection molding, extrusion molding, rolling granulation, slip casting, and casting molding, more preferably at least one of uniaxial pressing and isostatic pressing, even more preferably at least one of cold isostatic pressing and uniaxial pressing (powder press molding), and even more preferably cold isostatic pressing after uniaxial pressing.

[0107] Prior to sintering, a step of calcining the molded body to obtain a calcined body (hereinafter, also referred to as a "calcining step") may be included. By calcining the molded body, the binder can be removed from the molded body.

[0108] The conditions for the calcination step may be any as long as the zirconia sintered body of this embodiment can be obtained, but examples include heat treatment in an air atmosphere at 400° C. or higher and lower than 1100° C.

[0109] In the sintering step, the molded body or the calcined body is sintered to obtain a sintered body. Any sintering method can be used as long as the sintering proceeds, and examples of such methods include known sintering methods such as atmospheric sintering, pressure sintering, and vacuum sintering. As a preferred sintering method, atmospheric sintering is used, and since it is simple, it is preferable to use only atmospheric sintering. This allows the zirconia sintered body of this embodiment to be obtained as a so-called atmospheric sintered body. The atmospheric sintering is a method in which no external force is applied to the molded body (or the calcined body) during sintering, and the sintered body is sintered by simply heating it. Note that the composition of the powder of germanium oxide-containing stabilized zirconia, the calcined body of germanium oxide-containing stabilized zirconia, and the sintered body of germanium oxide-containing stabilized zirconia may be considered to be the same.

[0110] The conditions of normal pressure sintering include a sintering temperature of 1050°C to 1600°C, preferably 1100°C to 1550°C, 1100°C to 1500°C, or 1150°C to 1500°C. The sintering temperature is preferably higher than the calcination temperature. The sintering atmosphere may be at least one of an air atmosphere and an oxygen atmosphere, and preferably an air atmosphere. The heating rate may be 20°C / hour to 5000°C / hour. The sintering time may be appropriately set according to the amount and size of the sintered material to be sintered and the characteristics of the sintering furnace, and may be, for example, held at the above sintering temperature for 0.3 hours to 20 hours, 0.5 hours to 20 hours, or 0.5 hours to 15 hours.

[0111] Any method for producing zirconia may be used in the method for producing the zirconia sintered body of the present embodiment. One example of the method for producing zirconia includes a method including a step of heat-treating a composition containing a zirconia sol containing crystalline zirconia whose main phase is monoclinic zirconia and a stabilizing element source at 600° C. to 1250° C. to obtain a calcined powder, and a step of pulverizing the calcined powder.

[0112] The manufacturing method will be specifically described below, but the manufacturing method of zirconia in this embodiment is not limited thereto.

[0113] The method for producing the zirconia sol containing crystalline zirconia whose main phase is monoclinic zirconia is arbitrary, and at least one of a hydrothermal synthesis method and a hydrolysis method can be exemplified. In the hydrothermal synthesis method, a coprecipitate obtained by mixing a zirconium salt with an alkali or the like in the presence of a solvent is heat-treated at 100 to 200°C to obtain a zirconia sol. In the hydrolysis method, a zirconium salt is heated in the presence of a solvent to hydrolyze the zirconium salt, thereby obtaining a zirconia sol. Thus, the zirconia sol can be exemplified as a zirconia sol obtained by a hydrothermal synthesis method or a hydrolysis method, and a zirconia sol obtained by a hydrolysis method is preferable. A precursor used in the method for producing a zirconia sol can be a zirconium salt. The zirconium salt can be one or more selected from the group consisting of zirconium oxychloride, zirconium nitrate, zirconium chloride and zirconium sulfate, and is preferably at least one of zirconium nitrate and zirconium oxychloride, and more preferably zirconium oxychloride.

[0114] A calcined powder, which is a precursor of zirconia powder, is obtained by a process in which a composition (zirconia raw material composition) containing a zirconia sol containing zirconia whose main phase is monoclinic zirconia and a stabilizing element source is heat-treated at 600° C. or more and 1250° C. or less to form a calcined powder (hereinafter also referred to as a "powder calcination process").

[0115] In the powder calcination step, the heat treatment is performed at 500°C or more and 1250°C or less, and further at 600°C or more and 1250°C or less. By performing the heat treatment at 600°C or more, a powder that is easily densified by normal pressure sintering can be obtained. On the other hand, by performing the heat treatment at 1250°C or less, a powder that is easily dispersed by pulverization can be obtained. The heat treatment time may be appropriately changed depending on the heat treatment temperature, the amount of the zirconia raw material composition to be subjected to the treatment, and the characteristics of the heat treatment furnace, and may be, for example, 30 minutes to 6 hours. The rate of temperature rise to the heat treatment temperature has almost no effect on the calcined powder obtained, and the rate of temperature rise may be, for example, 50°C / hour to 1000°C / hour.

[0116] The heat treatment may be performed in any atmosphere, for example, any atmosphere selected from the group consisting of an oxidizing atmosphere, a reducing atmosphere, an inert atmosphere, and a vacuum atmosphere. An oxidizing atmosphere is preferable, and an air atmosphere is more preferable.

[0117] The zirconia raw material composition to be subjected to the powder calcination step may contain the above-mentioned zirconia sol and the stabilizing element source, and all or a part of the stabilizing element source may be dissolved in the zirconia sol. For example, at least a part of the stabilizing element source may be dissolved in the zirconia sol by a method such as mixing a zirconium salt and the stabilizing element source and hydrolyzing the mixture, or mixing a zirconium salt, the stabilizing element source, and an alkali to form a coprecipitate.

[0118] In the pulverization process, the calcined powder is pulverized. Zirconia, which has a low content of stabilizing elements, is prone to cracking and chipping during sintering. In contrast, pulverizing the calcined powder tends to increase the yield during sintering.

[0119] The grinding method may be any method, and may be at least one of wet grinding and dry grinding. Wet grinding is preferable, and wet grinding using an aqueous dispersion medium with a pH of > 7.0 (i.e., basic) is preferable, and wet grinding using an aqueous dispersion medium with a pH of > 8.0 is more preferable. Specific examples of wet grinding include one or more selected from the group consisting of a ball mill and a continuous media stirring mill, and a ball mill is preferable. Wet grinding using an aqueous dispersion medium with a pH of > 7.0 (i.e., basic) makes it easier for a difference in hardness to occur between the surface and the inside of the sintered body.

[0120] The powder to be subjected to the pulverization step may be a calcined powder containing germanium oxide and optionally alumina, or a mixed powder containing a calcined powder, a germanium source, and optionally an alumina source. The germanium source may be the above-mentioned germanium source, and the alumina source may be the above-mentioned alumina source. An example can be given.

[0121] The conditions for pulverization using a ball mill include, for example, mixing the calcined powder with a solvent (e.g., at least one of water and alcohol, and further water) to form a slurry in which the mass ratio of the calcined powder to the mass of the slurry is 30% by mass or more and 60% by mass or less, and pulverizing the slurry using zirconia balls having a diameter of 0.5 mm to 15 mm as a pulverization medium. The pulverization time may be appropriately adjusted depending on the amount of the calcined powder to be subjected to the treatment, and may be, for example, 8 hours to 100 hours.

[0122] After the wet grinding, the mixture is dried by any method to obtain zirconia powder. Drying conditions include air atmosphere and 110°C to 130°C.

[0123] In order to improve the handling of the powder, the manufacturing method of the powder may include a step of granulating the powder (hereinafter, also referred to as a "granulation step"). Any method may be used for granulation, and an example is spray granulation of a slurry in which the powder is mixed with a solvent. The solvent is at least one of water and alcohol, and preferably water. The granulated powder (hereinafter, also referred to as "powder granules") has an average granule diameter of 30 μm to 80 μm, and furthermore, 50 μm to 60 μm, and a bulk density of 1.00 g / cm. 3 More than 1.50g / cm 3 Below that, 1.10g / cm 3 More than 1.45g / cm 3 The following are some of the reasons: EXAMPLES

[0124] The present disclosure will be described below with reference to examples, but the present disclosure is not limited thereto. (Monoclinic ratio and 2θ (400)t-(004)t ) A general X-ray diffraction device (Ultima IV, manufactured by RIGAKU) was used to obtain XRD patterns of the powder and sintered samples. The conditions for the XRD measurement when calculating the monoclinic crystal ratio are as follows:

[0125] Radiation source: CuKα radiation (λ=1.5418Å) Tube voltage: 45kV Tube current: 40mA Measurement mode: Continuous scan Scan speed: 4° / min Step width: 0.02° Measurement range: 2θ=26° to 33° Goniometer: Radius 185mm From the formula (1), the monoclinic crystal ratio (%) of the powder was calculated using the XRD pattern of the obtained powder, and the monoclinic crystal ratio F of the sintered surface was calculated using the XRD pattern of the sintered surface of the obtained sintered body. m,a The monoclinic rate F (%) of the central part of the obtained sintered body was calculated using the XRD pattern of the central part of the obtained sintered body. m,p (%) was calculated for each.

[0126] The XRD measurement conditions for calculating the difference in 2θ of the peak top corresponding to the (004) plane of tetragonal zirconia from the 2θ of the peak top corresponding to the (400) plane of tetragonal zirconia in the center of the sintered body are as follows:

[0127] Radiation source: CuKα radiation (λ=1.5418Å) Tube voltage: 45kV Tube current: 40mA Measurement mode: Continuous scan Scan speed: 2° / min Step width: 0.02° Measurement range: 2θ=72° to 76° Goniometer: Radius 185mm The patterns obtained by the above-mentioned XRD measurements were subjected to background subtraction and XRD peaks due to CuKα2 radiation (λ=1.5443 Å) removal using the integrated powder X-ray diffraction software “PDXL”, and the 2θ at the peak tops of the XRD peaks corresponding to the (004) and (400) planes of tetragonal zirconia, as well as their difference, were determined. (Vickers hardness) The hardness of the sintered body was measured by a Vickers hardness test according to JIS R1610: 2003. The measurement conditions for the Vickers hardness were as follows:

[0128] Sample thickness: 1.5±0.5mm Measurement load: 5kgf Example 1 A hydrated zirconia sol was obtained by hydrolysis reaction of an aqueous zirconium oxychloride solution. Yttrium chloride hexahydrate was added and mixed with the hydrated zirconia sol so that the yttrium concentration was 1.0 mol%. After mixing, the mixture was dried in an air atmosphere and calcined in an air atmosphere at 1000°C for 2 hours to obtain a calcined yttrium-stabilized zirconia powder. Germanium oxide was added to the calcined zirconia powder so that the germanium oxide concentration was 3.0 mol%, and then pure water was added to make a slurry, and ammonia water was added to adjust the pH to 9. The adjusted slurry was pulverized and mixed for 24 hours in a ball mill using zirconia balls as a milling medium. The slurry after pulverization and mixing was dried in an air atmosphere at 110°C, and then sieved to remove coarse particles with an aggregate diameter exceeding 180 μm, thereby obtaining a powder of this embodiment consisting of zirconia containing 3.0 mol% germanium oxide and 1.0 mol% yttria.

[0129] Example 2 The powder of this example, which is made of zirconia containing 3.0 mol % germanium oxide and 1.2 mol % yttria, was obtained in the same manner as in Example 1, except that yttrium chloride hexahydrate was added to the hydrated zirconia sol so that the yttrium concentration was 1.2 mol %.

[0130] Example 3 The powder of this example, consisting of zirconia containing 4.0 mol% germanium oxide and 1.0 mol% yttria, was obtained in the same manner as in Example 1, except that germanium oxide was added to the calcined zirconia powder so that the germanium oxide concentration was 4.0 mol%.

[0131] Example 4 The powder of this example, consisting of zirconia containing 0.25 mass% alumina, 4.0 mol% germanium oxide, and 1.0 mol% yttria, was obtained in the same manner as in Example 1, except that the calcined powder and the mixed powder of alumina and germanium oxide were ball milled so that the alumina content was 0.25 mass% and the germanium oxide content was 4.0 mol%.

[0132] Example 5 The powder of this example, consisting of zirconia containing 10 mass% alumina, 1.8 mol% germanium oxide, and 1.2 mol% yttria, was obtained in the same manner as in Example 1, except that yttrium chloride hexahydrate was added to the hydrated zirconia sol so that the yttrium concentration was 1.2 mol%, and the mixed powder of the calcined powder and alumina and germanium oxide was ball milled so that the alumina content was 10 mass% and the germanium oxide content was 1.8 mol%.

[0133] Comparative Example 1 The powder of this comparative example, made of zirconia containing 3.0 mol% yttria, was obtained in the same manner as in Example 1, except that yttrium chloride hexahydrate was added to the hydrated zirconia sol so that the yttrium concentration was 3.0 mol%, and germanium oxide was not added to the calcined zirconia powder.

[0134] Comparative Example 2 The powder of this comparative example was obtained in the same manner as in Example 1, except that yttrium chloride hexahydrate was added to the hydrated zirconia sol so that the yttrium concentration was 3.0 mol%, and germanium oxide was added to the calcined zirconia powder so that the germanium oxide concentration was 0.3 mol%.

[0135] Comparative Example 3 The powder of this comparative example, which was made of zirconia containing 1.2 mol% yttria, was obtained in the same manner as in Example 1, except that yttrium chloride hexahydrate was added to the hydrated zirconia sol so that the yttrium concentration was 1.2 mol%, and germanium oxide was not added to the calcined zirconia powder.

[0136] The evaluation results of the powders of these Examples and Comparative Examples are shown in Table 1.

[0137] [Table 1]

[0138] In the above table, a "-" in the columns for stabilizing element content and additives indicates that the stabilizing element or additive is not included.

[0139] Example 6 The powder of Example 1 was subjected to uniaxial pressing at a pressure of 50 MPa and cold isostatic pressing (CIP) at a pressure of 196 MPa to form a disk-shaped compact.

[0140] Thereafter, the obtained molded body was sintered under the following conditions to obtain a sintered body of this example made of zirconia containing 3.0 mol % of germanium oxide and 1.0 mol % of yttrium oxide. The sintering conditions are shown below.

[0141] Sintering method: Pressureless sintering Sintering atmosphere: Air Sintering temperature: 1300℃ Sintering time: 2 hours Example 7 A sintered body of this example was obtained, which was made of zirconia containing 3.0 mol % germanium oxide and 1.0 mol % yttrium oxide, in the same manner as in Example 6, except that the obtained molded body was sintered at 1350°C.

[0142] Example 8 A sintered body of this example was obtained, which was made of zirconia containing 3.0 mol % germanium oxide and 1.0 mol % yttrium oxide, in the same manner as in Example 6, except that the obtained molded body was sintered at 1400°C.

[0143] Example 9 A sintered body of this example was obtained, which was made of zirconia having a germanium oxide content of 3.0 mol% and an yttrium oxide content of 1.2 mol%, in the same manner as in Example 6, except that the powder described in Example 2 was used and the obtained molded body was sintered at 1350°C.

[0144] Example 10 A sintered body of this example was obtained, which was made of zirconia having a germanium oxide content of 3.0 mol% and an yttrium oxide content of 1.2 mol%, in the same manner as in Example 6, except that the powder described in Example 2 was used and the obtained molded body was sintered at 1400°C.

[0145] Example 11 A sintered body of this example was obtained, which was made of zirconia containing 4.0 mol % germanium oxide and 1.0 mol % yttrium oxide, in the same manner as in Example 6, except that the powder described in Example 3 was used.

[0146] Example 12 A sintered body of this example was obtained, which was made of zirconia having a germanium oxide content of 4.0 mol% and an yttrium oxide content of 1.0 mol%, in the same manner as in Example 6, except that the powder described in Example 3 was used and the obtained molded body was sintered at 1350°C.

[0147] Example 13 A sintered body of this example was obtained, which was made of zirconia having a germanium oxide content of 4.0 mol% and an yttrium oxide content of 1.0 mol%, in the same manner as in Example 6, except that the powder described in Example 3 was used and the obtained molded body was sintered at 1400°C.

[0148] Example 14 A sintered body of this example was obtained, which was made of zirconia having an alumina content of 0.25 mass%, a germanium oxide content of 4.0 mol%, and an yttrium oxide content of 1.0 mol%, in the same manner as in Example 6, except that the powder described in Example 4 was used.

[0149] Example 15 A sintered body of this example was obtained, which was made of zirconia having an alumina content of 10 mass%, a germanium oxide content of 1.8 mol%, and an yttrium oxide content of 1.2 mol%, in the same manner as in Example 6, except that the powder described in Example 5 was used and the obtained molded body was sintered at 1350°C.

[0150] Comparative Example 4 A sintered body of this example made of zirconia with an yttrium oxide content of 3.0 mol% was obtained in the same manner as in Example 6, except that the powder described in Comparative Example 1 was used and the obtained molded body was sintered at 1550°C.

[0151] Comparative Example 5 A sintered body of this example was obtained, which was made of zirconia having a germanium oxide content of 0.3 mol% and an yttrium oxide content of 3.0 mol%, in the same manner as in Example 6, except that the powder described in Comparative Example 2 was used and the obtained molded body was sintered at 1400°C.

[0152] Comparative Example 6 Sintering was carried out in the same manner as in Example 6, except that the powder described in Comparative Example 3 was used.

[0153] The evaluation results of the sintered bodies of these Examples and Comparative Examples are shown in Table 2. For the evaluation, the Vickers hardness of the hardened surface of the main surface (the surface with a diameter of 20 mm) of the sintered body (disk shape with a diameter of 20 mm and a thickness of 2 mm) was measured. After that, the main surface was ground by 0.3 mm in the depth direction using a surface grinder, and then polished to a mirror finish by polishing with an abrasive cloth, polishing with a diamond slurry with an average particle size of 3 μm, and polishing with colloidal silica with a particle size of 0.03 μm in that order, and the Vickers hardness of the polished surface was measured.

[0154] [Table 2]

[0155] In the above table, "-" in the columns for stabilizing element content and additives indicates that the stabilizing element or additive is not included. Figure 3 shows the XRD patterns of the hardened surface and center of Example 6. From Figure 3, it can be seen that the XRD patterns of the hardened surface and center of the sintered body of Example 6 are significantly different. Figure 4 shows the Vickers indentation marks after measuring the Vickers hardness of the hardened surface and center of Example 6. Using the diagonal length of the Vickers indentation marks in Figure 4, the Vickers hardness of the hardened surface and center was calculated from formula (3).

[0156] From the above table, it can be confirmed that the sintered bodies of Examples 6 to 15 have a monoclinic ratio of more than 80% on the burned surface, while the monoclinic ratio in the center is less than 10%, and the hardness increase rate is greater than 0, that is, the Vickers hardness is higher in the center than in the burned surface. On the other hand, for the sintered bodies of Comparative Examples 1 and 2, the monoclinic ratio is less than 10% in both the burned surface and the center, the Vickers hardness of the center and the burned surface is almost the same, and no decrease in the Vickers hardness of the burned surface was confirmed. The appearance of the sintered bodies of Example 6 and Comparative Example 6 is shown in FIG. 5. As shown in FIG. 5, it can be confirmed that cracks have occurred throughout the sintered body of Comparative Example 6. Such cracked sintered bodies are difficult to use in various applications, and are also difficult to evaluate, grind, and polish, so the monoclinic ratio and hardness of Comparative Example 6 were not measured. FIG. 6 is a cross-sectional SEM image of the sintered body of Example 12. It can be seen that there is a sintered surface of about 10 μm thickness on the surface side of the sintered body at the top of the image, and a central part below it. It can be seen that there are vertical scratches at the time of cutting and a part with a different structure from the central part between the vertical scratches and the central part in the sintered surface part. Figure 7 shows the XRD patterns on the high angle side of the central part of Example 12 and Comparative Example 5. It can be seen that the distance between the peak tops of the two peaks in Example 12 is wider than the two peaks in Comparative Example 5.

[0157] From the above, it was confirmed that the sintered body of this example has a lower hardness in the sintered surface compared to the center. The sintered surface with low hardness is excellent in workability, while the center after processing has a high hardness, and therefore it can be said to have excellent mechanical properties such as wear resistance.

[0158] [Table 3]

[0159] Measurement example (hydrothermal degradation test) The surfaces of the zirconia sintered bodies of Examples 7, 12, 14, and 15 were polished to obtain polished surfaces. The polished sintered bodies were immersed in hot water at 140°C for 24 hours, and the monoclinic ratio of the polished surface was measured before and after immersion. The results are shown in the table below.

[0160] [Table 4]

[0161] From the above table, the monoclinic crystal ratio before hot water immersion is 2θ (400)-(004) The sintered body with a 2θ value of 1.70 or more is low. (400)-(004) It can be seen that the 2θ (400)-(004) It was confirmed that sintered bodies with a σ of 1.73 or more, and even 1.76 or more, had a low monoclinic rate after immersion in hot water, and were particularly resistant to hydrothermal degradation. [Explanation of symbols]

[0162] 100 Zirconia sintered body 11 Sintered body surface (polished surface) 12 Sintered body surface (burned surface) 13 Center 14 Burnt Skin 15 Depth direction

Claims

1. A zirconia sintered body containing a stabilizing element in an amount of more than 0% and less than 2.0 mol%, wherein the monoclinic ratio in the sintered surface of the sintered body is F m,a , the monoclinic rate in the center of the sintered body is F m,p Then, F m,a is 50% or more, and F m,a >F m,p The zirconia sintered body is

2. A zirconia sintered body containing a stabilizing element in an amount of more than 0% and less than 2.0 mol%, wherein in an XRD pattern at a center portion of the sintered body, the difference 2θ between the 2θ of the peak top corresponding to the (400) plane of tetragonal zirconia and the 2θ of the peak top corresponding to the (004) plane of tetragonal zirconia is (400)t-(004)t The zirconia sintered body, wherein the zirconia sintered body has a zirconia sintering angle of 1.5° or more.

3. The zirconia sintered body according to claim 1 or 2, wherein the stabilizing element is one or more elements selected from the group consisting of yttrium, calcium, magnesium and lanthanoids.

4. The zirconia sintered body according to claim 1 or 2, which contains germanium oxide.

5. The zirconia sintered body according to claim 3, wherein the germanium oxide content is more than 0% and less than 8.0 mol%.

6. The zirconia sintered body according to claim 1 or 2, which contains alumina.

7. The zirconia sintered body according to claim 1 or 2, wherein the improvement in hardness before and after polishing is 3% or more.

8. 3. The method for producing a zirconia sintered body according to claim 1 or 2, comprising zirconia containing a stabilizing element and germanium oxide, the zirconia having a monoclinic rate of more than 80%, and a G / S ratio of 0.35 or more when the amount of the stabilizing element in the powder is S mol % and the amount of germanium oxide is G mol %, the method comprising sintering a powder in an air atmosphere at 1100° C. or more and 1500° C. or less for 0.3 hours or more and 20 hours or less.

9. A powder comprising zirconia containing a stabilizing element and germanium oxide, wherein the zirconia has a monoclinic rate of more than 80%, and when the amount of the stabilizing element in the powder is S mol % and the amount of germanium oxide is G mol %, the G / S ratio is 0.35 or more.

10. A method for producing a zirconia sintered body using the powder according to claim 9.

11. A member comprising the sintered body according to claim 1 or 2.

Citation Information

Patent Citations

  • Alumina-zirconia ceramic and its production method

    JP2006056746A

  • Machinable zirconia and method for producing the same

    JP2015127294A